Market segmentation to facilitate scaling of solar-based irrigation bundles in Ethiopia - International Water Management Institute (International Water Management Institute, 2024)
Despite the high potential of and strong demand for wider adoption of agricultural innovations in Ethiopia, scaling efforts have often been ineffective, and innovation adoption remains limited. Successful and sustainable innovation scaling requires co-identifying and co-developing best-fit solutions for farmers and other actors in the value chain. Bundling these solutions, such as solar-powered irrigation pumps, with pay-as-you-go financing has improved the enabling environment for adoption. Identifying the farmer segments interested in investing in such bundles and strengthening linkages along the irrigation value chains are essential for matching demand and supply and creating the conditions to reach scale.